An immunologic test for chronic rhinosinusitis based on free intranasal eosinophilic major basic protein. Issue 1 (29th September 2014) - Ponikau, Jens U.; Winter, Laurie A.; Kephart, Gail M.; Squillace, Diane L.; Hershcovitch, Matt D.; Moon, Seo; Sherris, David A.; Kern, Eugene B.; Gleich, Gerald J.; Kita, Hirohito
<x xml:space="preserve">Abstract</x> Background A histologic hallmark of chronic rhinosinusitis (CRS) is an eosinophilic inflammation, present with and without nasal polyposis and independent of atopy. Eosinophils migrate through nasal tissue including the epithelium into the nasal airway mucus, where they form clusters and degranulate, releasing granule proteins including the toxic major basic protein (MBP). Specific biomarkers for CRS, which could be used as a diagnostic test for CRS with a high sensitivity and specificity, are presently lacking. Recently, an enzyme‐linked immunosorbent assay (ELISA)‐based test for MBP in nasal airway mucus received regulatory approval. Methods A new assay was specifically developed to detect released MBP in airway mucus. MBP levels in nasal mucus of 85 randomly selected CRS patients diagnosed by endoscopy, computed tomography (CT) scans and symptoms were compared to 13 healthy controls and 5 disease controls (allergic rhinitis). Results Overall, 92% (78/85) of CRS patients' mucus were positive for MBP (mean 7722 ng/mL) vs none of 13 healthy controls and none of 5 allergic rhinitis patients (<7.8 ng/mL; p < 0.000000000002). In this study, the MBP ELISA had a 92% sensitivity and 100% specificity for CRS. Conclusion Free MBP in nasal mucus can be used as a biomarker to diagnose CRS. The MBP ELISA represents the first immunologically‐based test to potentially distinguish CRS from the eosinophilic inflammation in allergic rhinitis.